Crown Diameters of Deciduous Teeth in Jordanians - F. N. Hattab; A. S. Al-Momani; O. M. Yassin; M. A. O. Al-Omari; A. M. Hamasha; M. A. Rawashdeh; A. Tavas (Dental Anthropology Association, 1999)
Odontometric data on the deciduous dentition of Jordanians are lacking and such data on Arabs are generally scarce. The aim of this study was to provide a detailed description of crown-size dimensions in the deciduous dentition of Jordanians and to compare the findings with those of other populations. Measurements of mesiodistal (MD) and buccolingual (BL) crown diameters were obtained from dental casts of 84 males and females aged 2.9 to 5.8 years. The differences in crown size (MD and BL diameters) between the right and left sides of the dental arch were not significant. All antimeric teeth showed high correlation coefficients in their crown dimensions (p<0.001). These findings suggest that either right or left side measurements can be taken to represent the tooth size of the populations. The relative variability in crown size showed that the lateral incisors were the most variable teeth (coefficient of variation: CV=7.5%), while the second molars were the most stable teeth (CV=4.7%). The MD diameters were more variable in the males for all teeth except the mandibular first molars, whereas variabilities in BL dimensions showed a similar pattern in both sexes. No significant differences in crown size measurements were found between males and females. Male means exceeded female means only by 0.05 mm. The central incisors displayed the greatest percentage of sexual dimorphism, while the second molars were the least dimorphic teeth. No specific pattern of percentages of sexual dimorphism were noted between the MD and BL diameters. The percentage of sexual dimorphism in the present sample was considerably lower than those of other ethnic groups. Jordanian children had tooth size that was larger than their Egyptian and North American counterparts, close to those of Japanese, and smaller than those of British children.